LC-MS profiling and cytotoxic activity of Angiopteris helferiana against HepG2 cell line: Molecular insight to investigate anticancer agent. - Bipindra Pandey; Shankar Thapa; Mahalakshmi Suresha Biradar; Bhoopendra Singh; Jaya Bahadur Ghale; Pramod Kharel; Prabhat Kumar Jha; Ram Kishor Yadav; Sujan Dawadi; Poojashree V (PLoS ONE)
Liver cancer is one of the most prevalent malignant diseases in humans and the second leading cause of cancer-related mortality globally. Angiopteris helferiana was mentioned as a possible anticancer herb according to ethnomedicinal applications. However, the molecular docking and chemical profiling of the bioactive phytoconstituents accountable for the reported anticancer action still require research. The present study aims the phytochemical profiling and bioactivity evaluation of A. helferiana. The study design with in-vitro and in-silico technique of the LC-MS followed by a study of the ligand-protein interaction using the molecular docking method, and investigates the cytotoxic activity by MTT assay of A. helferiana bioactive compounds on HepG2 cell lines. LC-MS results detected seventeen phytoconstituents in A. helferiana extract belonging to variable chemical classes with most prevailing compounds such as Vicenin 1, Schafroside, Violanthin, Coumarin, Quercetin, Angiopterioside, and Corosolic acid. The finding concluded that Quercetin showed significant binding energy of -8.8 kcal/mol and then Schafroside also possesses the binding energy of -8.1 kcal/mol against the human PPAR-δ receptor (PDBID: 1I7G). The extract showed the moderate cytotoxic activity having IC50 value of 236.93 μg/mL. Our finding suggests that these bioactive compounds could be developed as promising anticancer agent, but further in-vivo study require to validate the finding along with isolation of individual phytoconstituents.